CITRA PEREMPUAN DALAM PERIBAHASA MINANGKABAU - Gusna Ronsi (Universitas Andalas, 2011)
This paper describes woman image in peribahasa Minangkabau. Data research were obtained from interview and literature observation. The peribahasa forms which contain woman image are gurindam, mamang, pepatah petitih, and seloka. The woman image in this forms are firm, kind, wise, deligent, and polite.